Behavioural Indicators of Intra- and Inter-Specific Competition: Sheep Co-Grazing with Guanaco in the Patagonian Steppe - Fernandez, Tomas; Lancaster, Alex; Moraga, Claudio A.; Radic Schilling, Sergio Javier; von Hardenberg, Achaz; Corti, Paulo (My University, 2021)
In extensive livestock ranching, where animals are maintained at high numbers, competition between individuals is expected, but not generally assumed. To compensate for reduced food availability, herbivores modify their feeding behaviour, which can be used as an indicator of competition. We investigated behavioural changes of domestic sheep in Chilean Patagonia in response to herd size, food availability, and the presence of a wild competitor, the guanaco, considered a problem for sheep production by ranchers. Large sheep herds were associated with a decrease in sheep grazing, while food availability increased time spent feeding. Guanaco had no effect on sheep behaviours. Behavioural changes were mostly associated with competition between individual sheep and not with guanaco. We suggest that to improve sheep production, ranchers should focus on sheep management at appropriate herd sizes according to grassland capacities. In extensive livestock production, high densities may inhibit regulation processes, maintaining high levels of intraspecific competition over time. During competition, individuals typically modify their behaviours, particularly feeding and bite rates, which can therefore be used as indicators of competition. Over eight consecutive seasons, we investigated if variation in herd density, food availability, and the presence of a potential competitor, the guanaco (Lama guanicoe), was related with behavioural changes in domestic sheep in Chilean Patagonia. Focal sampling, instantaneous scan sampling, measures of bite and movement rates were used to quantify behavioural changes in domestic sheep. We found that food availability increased time spent feeding, while herd density was associated with an increase in vigilant behaviour and a decrease in bite rate, but only when food availability was low. Guanaco presence appeared to have no impact on sheep behaviour. Our results suggest that the observed behavioural changes in domestic sheep are more likely due to intraspecific competition rather than interspecific competition. Consideration of intraspecific competition where guanaco and sheep co-graze on pastures could allow management strategies to focus on herd density, according to rangeland carrying capacity.
Keywords: density; feeding behaviour; bite rate; intraspecific competition; interspecific competition; guanaco; sheep